A Comparison of the Effect of One, Three, or Six Weeks of Immobilization on Function and Pain After Open Reduction and Internal Fixation of Distal Radial Fractures in Adults: A Randomized Controlled Trial. (5th July 2018) - Watson, Narelle; Haines, Terrence; Tran, Phong; Keating, Jennifer L.
Abstract : Background: The optimum period of immobilization following open reduction and internal fixation (ORIF) of distal radial fractures has not been established. Methods: One hundred and thirty-three adults with a distal radial fracture treated with ORIF (using a volar locked plate) were randomly allocated, with stratification according to age, to 1, 3, or 6 weeks of postoperative immobilization in a parallel-design, assessor-blinded, randomized controlled trial (RCT). After cast removal, a standardized education and exercise program was followed for 6 weeks. Primary outcomes were function (according to the Patient-Rated Wrist Evaluation [PRWE]), worst (visual analog scale [VAS]-W) and usual (VAS-U) pain in the past week, and active wrist extension and forearm supination range of motion. All measures were recorded at 6, 12, and 26 weeks following surgery. Secondary outcomes were wrist flexion, radial deviation, ulnar deviation, and forearm pronation active range of motion; function (Disabilities of the Arm, Shoulder and Hand [DASH]); grip strength; postoperative adverse events; return to work and/or usual daily activities; and compliance with the home exercise program. Results: More than 90% of the participants received treatment as allocated, and 87% completed the 6-month follow-up. At 6 weeks, both the 1-week and 3-week groups had significantly better PRWE scores, wrist extension, and flexion active range of motion than the 6-week group. However, no treatment group was superior to another with respect to primary or secondary outcomes at 12 weeks or 6 months following surgery. Analyses considering only the main effect of the intervention group indicated a preference for the 3-week group, which performed significantly better than the 6-week group with respect to the PRWE, pain (VAS-W and VAS-U), wrist flexion, ulnar deviation, forearm pronation active range of motion, and DASH score. Conclusions: For patient function, range of motion, and pain, this investigation demonstrated that immobilization periods of 1 and 3 weeks produced superior short-term outcomes compared with those after 6 weeks of immobilization. These differences were not evident at 3 and 6 months following surgery, with the immobilization period having no significant effect on long-term function, range of motion, or pain. There were no significant differences in adverse events associated with shorter immobilization periods. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.